Fragment-based discovery of a new family of non-peptidic small-molecule cyclophilin inhibitors with potent antiviral activities - Abdelhakim Ahmed-Belkacem (Nature Portfolio, 2016)
Cyclophilins play a key role in the life cycle of many viruses and represent important drug targets for broad-spectrum antiviral therapies. Here, the authors use fragment-based drug discovery to develop non-peptidic inhibitors of human cyclophilins with high activity against replication of a number of viral families.